Designing a holistic model of faculty development program for the College of Nursing and Midwifery, De La Salle University, Dasmarinas, Cavite - Marcial, Joselita F. (2000)
As faculty members in the university setting, nurse educators have been faced with various trends in the local and global situations. The University responds to these trends by aiming to produce well-rounded graduates. This places the responsibility upon the faculty to be also well-rounded educators. Among health professions (HP) educators, this became a challenge. The overall objective of this project was to develop a holistic design of faculty development for nurse educators. Specifically, the study aimed 1) to produce a list of comprehensive training needs of nurse educators at the De La Salle University College of Nursing and 2) to present a holistic design composed of a general blueprint and samples of some specific instructional units for each training area identified. Initial information about the holistic training of HP educators was derived from topics of conversations among HP faculty, from fora and conferences, and expressions from the nurse educators of De La Salle University-Dasmarinas (DLSU). This was followed by using formal needs assessment methods aimed at identifying faculty needs. The qualitative, descriptive research method was used. The study population was composed of all the 33 nurse educators of DLSU-D as key respondents and their dean and selected students as general respondents. Records and documents that contained the faculty profile tasks performed by faculty and their suggestions for training were reviewed. Then the faculty were further allowed to voice out their needs through faculty meetings and focus group discussions. The needs they identified were comprehensive. Information from them was corroborated by comments from the dean and the students. The overall findings pointed to faculty needs that covered comprehensive training areas: teaching, personal-professional, organization/co-curricular, and research. Findings were analyzed using the four-step method of qualitative data analysis of M. Leininger (1991). These findings became the basis of the comprehensive training areas included in the faculty development design. Based on the findings and the design made, it was concluded that the area on development of teaching skills was still a top need; this was followed by the need to be trained in other areas which also have impact on teaching like personality development, organizational skills, and research skills development. Overall, faculty members such as nurse educators are concerned with holistic training. The study recommended the following: continuous needs assessment of faculty; updating of the design as needs constantly change; a faculty development project coordinator to take charge of implementation; an evaluation scheme to appraise impact training; and a strong institutional support. The blueprint was complemented by a more specific training unit for each area. Then sample instructional units of specific topics were incorporated in each training unit.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: College of Nursing and Midwifery. De La Salle University Dasmarinas; Curriculum planning